2007
DOI: 10.1111/j.1440-1746.2006.04614.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus (HCV) viremia in HIV‐infected patients without HCV antibodies detectable by third‐generation enzyme immunoassay

Abstract: The HCV viremia and no detectable HCV antibodies by third-generation immunoassay were found only in individuals with a CD(4) count of <100 cells/mm(3). Molecular assays to detect HCV-RNA should be considered as an important tool to diagnose hepatitis C in HIV-1-infected patients with advanced immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…RT-PCR should still be considered a confirmatory test when the patient tests positive for anti-HCV or if ALT levels are persistently abnormal in patients who are anti-HCV-negative in the absence of another etiology [89]. Moreover, HCV-RNA should be considered as an important tool to diagnose HCV in HIV-infected patients with advanced immunosuppression (CD4 count of <100 cells/mm 3 ) [101]. It is also noteworthy that a single negative anti-HCV test cannot rule out HCV infection in the HD population because of the potential latency between infection and seroconversion as well as the possible lower sensitivity of ELISA in HD patients as discussed above.…”
Section: Diagnostic Featuresmentioning
confidence: 99%
“…RT-PCR should still be considered a confirmatory test when the patient tests positive for anti-HCV or if ALT levels are persistently abnormal in patients who are anti-HCV-negative in the absence of another etiology [89]. Moreover, HCV-RNA should be considered as an important tool to diagnose HCV in HIV-infected patients with advanced immunosuppression (CD4 count of <100 cells/mm 3 ) [101]. It is also noteworthy that a single negative anti-HCV test cannot rule out HCV infection in the HD population because of the potential latency between infection and seroconversion as well as the possible lower sensitivity of ELISA in HD patients as discussed above.…”
Section: Diagnostic Featuresmentioning
confidence: 99%
“…For this reason, all HIV-infected patients should be monitored for the presence of anti-HCV antibodies (Hadlich et al 2007; Vachon et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…In a pooled analysis of four studies, the frequency of HCV RNA positivity and concomitant absence of anti-HCV antibodies among HIV-infected patients was 3.2 % (Chamie et al 2007); in one study, it was reported to be as high as 13.2 % (Bonacini et al 2001; George et al 2002; Hadlich et al 2007). Seronegative HCV infection in HIV-infected individuals is more common in patients with CD4 + cells count below 100/μL and more advanced immunodeficiency (Hadlich et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…. In HIVþ patients with a low CD4 count (<200 cells/ mm 3 ) the EIA may be negative and HCV-RNA detection may be needed for diagnosis 175. .…”
mentioning
confidence: 99%